Efficacy of IgG and F(ab′)2 Antivenoms to Neutralize Snake Venom-induced Local Tissue Damage as Assessed by the Proteomic Analysis of Wound Exudate - Rucavado Romero, Alexandra (2012)
2082-01 Embargo por política editorial